The Influence of Regional Financial Statement Presentation and Financial Statement Accessibility on Transparency Through Accountability in Financial Statement Management of the Tabalong Regency Local Government Tapin Regency, South Kalimantan - Rahman, Yudi; Riya, Sity; Melania; Sutrisno; Kadir, Abdul (Archives of Business Research, 2024)
The aim of the research is to determine and analyze the influence of the presentation of regional financial reports and the accessibility of financial reports on transparency and accountability in the management of financial reports for the Tabalong Regency Regional Government. This type of research is quantitative causality research. The causal approach is to examine the cause-and-effect relationship between two or more variables. Causal research explains the effect of changes in value variations in one variable on variations in the values of other variables. The data analysis technique used is with the help of SEM PLS. The results of the research show that the presentation of regional financial reports has a significant influence on the transparency of Tabalong Regency, the accessibility of financial reports has a significant influence on the transparency of Tabalong Regency, the presentation of regional financial reports has a significant influence on the accountability of financial report management of the Tabalong Regency Regional Government, the accessibility of financial reports has a significant influence on the accountability of management of reports Tabalong Regency Regional Government Finances, Transparency Has a Significant Influence on the Accountability of Management of Financial Reports of the Tabalong Regency Regional Government. Presentation of Regional Financial Reports has a Significant Influence on the Accountability of Management of Financial Reports through Transparency of the Regional Government of Tabalong Regency. Accessibility of Financial Reports Has a Significant Influence on the Accountability of Financial Report Management through Regional Government Transparency Tabalong Regency.